Integrated crop management for cassava cultivation in Asia - Maung Aye, Tin; Howeler, Reinhardt H. (Burleigh Dodds Science Publishing Limited, 2017)
The demand for cassava in Asia is expected to grow in the years to come, largely because of an increasing demand for animal feed, biofuels and multiple uses of starch. Increasing the quantity and quality of cassava products in response to growing demand requires careful and sustainable increases in cassava production. This chapter describes good agricultural practices (GAP) in cassava cultivation, focusing on pre- and post-harvesting practices and measures to manage crop health, including ensuring soil fertility and weed, disease and pest control. The chapter addresses the challenge of encouraging farmers to adopt GAP and reviews likely future trends in this area.